1999
DOI: 10.1046/j.1365-2664.1999.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Clearcutting and burning of northern spruce‐fir forests: implications for small mammal communities

Abstract: Summary 0[ This study was designed to test the hypotheses that "i# abundance and related demographic parameters of small mammal populations would decline after clear! cutting of northern spruce!_r forest\ and "ii# prescribed burning\ following clear! cutting\ an approach to emulating natural disturbance\ would enhance the species richness and diversity of the small mammal community relative to unharvested and clearcut forests[ 1[ Intensive live!trapping of small mammal populations was conducted in replicated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
1
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 52 publications
(53 reference statements)
7
61
1
4
Order By: Relevance
“…The increasing coverage of a shrub and tree layer results in significant changes in community structure (non-forest species disappear), slow drop of abundance that again rises slightly until reaching a balanced stage in climax forest. Confirmation of particular phases of this scheme by empirical data was found in European forests (Grodziñski 1959, Kratochvíl and Gaisler 1967, Wo³k and Wo³k 1982 as well as in North America (Kirkland 1977, Ramirez and Hornocker 1981, Sullivan et al 1999. Also our data from the Smrk Mt complex clearly indicate an increase in abundance of the small mammal community after deforestation.…”
Section: Discussionsupporting
confidence: 82%
“…The increasing coverage of a shrub and tree layer results in significant changes in community structure (non-forest species disappear), slow drop of abundance that again rises slightly until reaching a balanced stage in climax forest. Confirmation of particular phases of this scheme by empirical data was found in European forests (Grodziñski 1959, Kratochvíl and Gaisler 1967, Wo³k and Wo³k 1982 as well as in North America (Kirkland 1977, Ramirez and Hornocker 1981, Sullivan et al 1999. Also our data from the Smrk Mt complex clearly indicate an increase in abundance of the small mammal community after deforestation.…”
Section: Discussionsupporting
confidence: 82%
“…Despite small mammals being recognized as biological indicators of sustainable forest management in the boreal zone (Pearce and Venier 2005), most research has focussed on changes in their communities during postdisturbance forest succession: after fires, clear cutting and logging (i.e., Gashwiler 1970;Kirkland 1990;Sullivan et al 1999;Briani et al 2004;Swanson et al 2010;Urban and Swihart 2011;Borchert et al 2014). Only a few investigations have dealt with changes in the small mammal community during meadow-to-forest succession stages (Atkeson and Johnson 1979;Huntly and Inouye 1987;Swihart and Slade 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Seedbed quality and dominant plant communities in insect-disturbed gaps and harvested gaps in GMNP are known to be very similar (Humber 2009) and seeds were always planted within a consistent seedbed. Further research is needed to investigate if the ubiquitously low emergence within anthropogenic gaps may potentially be the result of higher levels of seed predation in this disturbance regime (Simon et al 1998;Sullivan et al 1999), as remnants of predated seeds were occasionally observed within experimental plots.…”
Section: Discussionmentioning
confidence: 99%